LEMBAGA PENDIDIKAN ISLAM PERIODE AWAL DALAM PERSPEKTIF SEJARAH - Nyayu Soraya (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2016)
Education and teaching are first two activities performed by our prophet Muhammad (pbuh). Although the prophet's message is delivered through preaching method, the preaching method, the preaching itself is inseparable from education and teaching since the preaching is basically a cultivating effort of religious values and a call for human to practice them.The early development of Islamic education is simply boundless to the certain education rules. However the education institution is obviously needed to support the education process as proven in the prophet age.